Properties of Epoxy-Asphalt Pavement Mixture for Bridge Decks - Albayati, Amjad H.; Al-Azawee, Esraa T. (Al-Nahrain Journal for Engineering Sciences, 2018)
Improving the ability of asphalt pavement to survive the heavily repeated axle loads and weathering challenges in Iraq has been the subject of research for many years. The critical need for such data in the design and construction of more durable flexible pavement in bridge deck material is paramount. One of new possible steps is the epoxy asphalt concrete, which is classified as a superior asphalt concrete in roads and greatly imparts the level of design and construction. This paper describes a study on 40-50 penetration graded asphalt cement mixed with epoxy to produce asphalt concrete mixtures. The tests carried out are the Marshall properties, permanent deformation, flexural fatigue cracking and moisture damage. Epoxy asphalt mixes performed better on resistance to fatigue and permanent deformation. They also performed significantly better on low-temperature properties and resistance to moisture damage. The addition of 30 percent of epoxy (by weight of asphalt cement) resulted in increase of Marshall stability by 39.8 percent, improve the tensile strength ratio by 22.9 percent, lowering both the rate of permanent deformation by 26.8 percent and the fatigue accumulation coefficient by 53.5 percent, in comparison with control HMA. Based on the above findings, it is recommended to use epoxy asphalt mixes as an optimal material for paving bridges deck in Iraq since it showed good prospects for this application due to the valuable performance and durability improvement.